Morphological Characterization of Selected Sesame (Sesamum Indicum L.) Genotypes in Western Kenya - Koitilio , B; Kinyua , M; Kiplagat , O.; Pkania , K; Kimno , S. (African Journal of Education,Science and Technology (AJEST), 2018)
Sesame is one of the most important oilseed crops in the tropical and subtropical regions of the world. Despite its importance, sesame yields in Kenya are very low due to lack of improved and high yielding varieties as well as insufficient variety information regarding genetic diversity. The objective of this study was to evaluate the diversity in morphological characters of sesame in Western Kenya. A high level of genetic diversity based on morphological traits was observed which could be attributed to a wide range of environmental conditions which induces variability through genotype by environment interaction. The dendrogram based on UPGMA cluster analysis did not separate the genotypes based on their geographical distribution instead grouped them according to their morphological differences. PCA showed that the first four principal components were important and indicated that number of capsule/plant, number of fruiting branches/plant, seed yield/plant, leaf arrangement, leaf hairiness and flower color were the most important characters and hence were most useful for distinguishing sesame genotypes. Genotypes UG1 and KSS showed better yield performance across the three environments. The use of these genotypes in breeding programs would contribute to improving sesame varieties with a high seed yield and hence improved food security. This research study, therefore, provides important insights into the diversity in morphological traits of sesame genotypes in Western Kenya and constitutes a set of useful genetic background information that can be used as a basis for future breeding strategies and sesame improvement programs.